Internal Audit Quality, Audit Committee, and Its Influence on Financial Reporting Quality - Riyanto, Naomi Fani; Rapina, Rapina (Universitas Pamulang, 2024)
This research aims to determine the extent to which internal audit quality and the audit committee influence the quality of financial reporting. The type of research conducted in this study is explanatory research. The study population consists of staff working in manufacturing, finance, education, and service companies in Indonesia. Non-probability sampling using snowball sampling was employed to select a sample of 57 respondents. The data used are primary data, processed through Smart-PLS Version 4. The research employs partial least squares (PLS) structural model analysis. The stages of testing the structural model include forming the structural model, assessing its feasibility, and evaluating the significance of variable effects. The findings show that the quality of internal audits and the audit committee influence the quality of financial reporting.